Thermodynamic investigations on compounds of ZnO-V2O5 system. (December 2021) - Phapale, S.; Dawar, R.; Pathak, P.; Achary, S.N.; Mishra, R.
Abstract: In the present paper, thermodynamic properties of compounds of ZnO-V2 O5 system have been reported. Phase pure compounds of ZnO-V2 O5 system viz., ZnV2 O6, Zn2 V2 O7, Zn3 V2 O8 and Zn4 V2 O9 have been prepared and characterized. The standard molar enthalpies of formation of these compounds at 298 K ( ∆ f H 298 o ) and their isobaric heat capacity were determined employing calorimetric techniques. From their enthalpy of formation and the temperature dependent molar heat capacity data, thermodynamic functions of ZnV2 O6 (s), Zn2 V2 O7 (s), Zn3 V2 O8 (s) and Zn4 V2 O9 (s) compounds have been derived. From these derived thermodynamic parameters, the relative stabilities of the compounds were determined. Graphical Abstract: ga1 Highlights: Enthalpy of formation of compounds in ZnO-V2 O5 system at 298 K has been determined. Cp o of these compounds has been measured in temperature range 300–600 K. Thermodynamic functions of Znn V2 O5+n (cr) compounds (n = 1, 2, 3, 4) have been derived. Thermodynamic stability of these compounds is reported for the first time.